2021
DOI: 10.3390/diagnostics11050884
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Cerebrospinal Fluid Plasma-Derived Proteins of Neurological Patients

Abstract: Background and aims: Cerebrospinal fluid (CSF) protein content presents a sexual dimorphism in humans. We investigated sex-related differences in CSF IgG levels and in the quantification of intrathecal IgG synthesis (IIS). Methods: CSF, serum albumin and IgG were measured in 1519 neurological patients and both linear and hyperbolic formulas were used for the quantification of IIS. CSF-restricted oligoclonal IgG bands (OCBs) were used as “gold standard”. Results: The linear IgG Index showed a weak agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Besides the fact that males have a different composition of CSF serum-derived proteins than females, CSF flow dynamics are also sex-dependent [ 18 , 19 ]. Presumably, this is the case in our model too, where the proinflammatory cytokines were given at a speed comparable to that of the physiological CSF flow.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the fact that males have a different composition of CSF serum-derived proteins than females, CSF flow dynamics are also sex-dependent [ 18 , 19 ]. Presumably, this is the case in our model too, where the proinflammatory cytokines were given at a speed comparable to that of the physiological CSF flow.…”
Section: Discussionmentioning
confidence: 99%
“…This way of carrying out biomedical research has made it possible to highlight differences that were previously existent but which had not yet been taken into consideration. In the case of CSF analysis for the classification of the neurological patient, a sex-specific approach to laboratory data has, in recent years, shown a greater permeability of BCSFB in males compared to females with a consequent increase in protein transferred from the blood to CSF [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this remains a key point to understand because, in both cases, we may either be overestimating the altered BCSFB permeability in the male or, on the contrary, underestimating it in the female. We have recently demonstrated that not only albumin but also serum IgG are more concentrated in males than in females CSF [ 17 ]. In the present study, we tried to understand if this increased BCSFB permeability to serum IgG can somehow impact the quantitative and qualitative determination of the intrathecal IgG synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations